Penyuluhan Dan Demonstrasi Tentang Perawatan Payudara Pada Ibu Menyusui Di Puskesmas Labuhan Rasoki Kecamatan Padangsidimpuan Tenggara Kota Padangsidimpuan Tahun 2020 - Lola Pebrianthy; Nefonavratilova Ritonga; Giopani Simbolon (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Counseling activities and demonstrations on breast care in nursing mothers in the Puskesmas Labuhan Rasoki District Padangsidimpuan Southeast Padangsidimpuan city aims to increase the knowledge of nursing mothers about breast care in nursing mothers. Breast care during pregnancy is one of the important parts that should be considered as a preparation in breast-feeding. Community service is done by providing information about breast care and how to do breast care with the number of participants as many as 15 people. The results of the evaluation during the process of the activity was obtained almost all participants have understood and know how to do breast care that is bai and correct. With this health education, it is expected to improve the knowledge and skills of nursing mothers about payuadra care and how to do payuadara care so that nursing mothers do not experience interference in the breastfeeding process so that exclusive breastfeeding programs can be achieved.